2001
DOI: 10.1897/1551-5028(2001)020<0763:tatozu>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and Toxicity of Zinc Under Time-Varying Exposure in the Guppy (Poecilia Reticulata)

Abstract: Levels of toxic substances released into the environment are often highly variable and fluctuate over time. The present study deals with a simple type of time-variable exposure, diluted pulse. We determined toxicokinetic parameters of zinc in guppy fish (Poecilia reticulata) and evaluated the applicability of a toxicokinetics-based survival model developed earlier. In the toxicokinetics experiment, zinc was rapidly taken up and released again; the half-life in fish was only 1.5 d. In the toxicity experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Mucus also plays an important role in protecting fish skin against waterborne heavy metals such as Zn. Zn was chosen because (1) it is an essential microelement (Watanabe et al 1997) present in every cell and involved in the structure or function of more than 300 enzymes and proteins (Vallee & Falchuk 1993, Cousins 1998; (2) at elevated concentrations, it becomes an important toxicant (Widianarko et al 2000(Widianarko et al , 2001; (3) it is one of the most common aquatic pollutants (Bowen et al 2006), affecting both fish (Atchison et al 1987, Bowen et al 2006) and parasites (Sures 2002, Morley et al 2003a,b, Thielen et al 2004) in many ways; and (4) the reported toxic concentrations for fish and parasites are within the same order of magnitude, whereas other heavy metals are much more toxic for the fish than for aquatic stages of parasites (Cross et al 2001, Canadian Council of Ministers of the Environment 2005, Pietrock & Goater 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucus also plays an important role in protecting fish skin against waterborne heavy metals such as Zn. Zn was chosen because (1) it is an essential microelement (Watanabe et al 1997) present in every cell and involved in the structure or function of more than 300 enzymes and proteins (Vallee & Falchuk 1993, Cousins 1998; (2) at elevated concentrations, it becomes an important toxicant (Widianarko et al 2000(Widianarko et al , 2001; (3) it is one of the most common aquatic pollutants (Bowen et al 2006), affecting both fish (Atchison et al 1987, Bowen et al 2006) and parasites (Sures 2002, Morley et al 2003a,b, Thielen et al 2004) in many ways; and (4) the reported toxic concentrations for fish and parasites are within the same order of magnitude, whereas other heavy metals are much more toxic for the fish than for aquatic stages of parasites (Cross et al 2001, Canadian Council of Ministers of the Environment 2005, Pietrock & Goater 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we hypothesized that the evidence of acclimation of the epidermal tissue observed in response to Zn alone (Gheorghiu et al 2009) would also be observed in response to the combined stresses of Zn and infection. Guppies are useful test animals in aquatic experiments because they are easy to maintain and breed under laboratory conditions and they are able to survive at very high concentrations of Zn (Widianarko et al 2000(Widianarko et al , 2001. Also, G. turnbulli burdens can be repeatedly monitored over time on individual hosts, as the parasites only live on the skin and fins.…”
Section: Introductionmentioning
confidence: 99%
“…We suppose that when saturation occurs, the kinetics is a linear one-compartment kinetics with an upper limit value for the elimination rate. In this way, Widianarko et al [24] showed that for the guppy Poecilia reticulata, the one-compartment kinetics could apply to relatively high concentrations of zinc. Moreover, the survival data we obtained during the depuration period would probably not have been predicted correctly if the elimination of the compound had been different from the one used in the model.…”
Section: Kineticsmentioning
confidence: 99%
“…Thus sloughing of mucous and epidermal cells also serves as a mechanism to remove any Zn that may have been absorbed into these cells (Shephard, 1994). Both mucous release onto the surface and sloughing of cells may contribute to the high tolerance of P. reticulata to Zn (Widianarko et al, 2000(Widianarko et al, , 2001. The positive correlation between tissue concentration of Zn and concentration of Zn in the sediment of urban streams from which P. reticulata had been collected (Widianarko et al, 2001), and the ability of P. reticulata to survive with tissue concentrations of Zn that were 15-fold higher than normal (Widianarko et al, 2000) indicate that additional physiological adaptations, probably including elevated MT levels, are also involved.…”
Section: S T H E R E E V I D E N C E O F Ac C L I M At I O N O F T mentioning
confidence: 99%
“…concentrations of zinc (15-fold normal body concentration) without endangering their survival (Widianarko et al, 2000(Widianarko et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%